The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12968/bjon.2014.23.10.514
|View full text |Cite
|
Sign up to set email alerts
|

The art of noticing: essential to nursing practice

Abstract: Noticing is integral to the everyday practice of nurses; it is the pre-cursor for clinical reasoning, informing judgement and the basis of care. By noticing the nurse can pre-empt possible risks or support subtle changes towards recovery. Noticing can be the activity that stimulates action before words are exchanged, pre-empting need. In this article, the art of noticing is explored in relation to nursing practice and how the failure to notice can have serious consequences for those in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The literature indicated that nursing students need the necessary support to understand and articulate what they notice and to recognize its relevance. [34,38] The clinical instructor can coach students throughout the clinical day while undertaking patient care responsibility and during the post-conference when debriefing and reflecting on daily encounters. Students' active engagement in these debriefings will enhance the "narrative-reflective" reasoning pattern, [32] formally identified by Tanner [34] as the "narrative" reasoning style.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature indicated that nursing students need the necessary support to understand and articulate what they notice and to recognize its relevance. [34,38] The clinical instructor can coach students throughout the clinical day while undertaking patient care responsibility and during the post-conference when debriefing and reflecting on daily encounters. Students' active engagement in these debriefings will enhance the "narrative-reflective" reasoning pattern, [32] formally identified by Tanner [34] as the "narrative" reasoning style.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement in clinical judgment parallels what other authors have termed as "noticing". [23,38] Noticing is the ancestor for both clinical reasoning and clinical judgment. It is only possible when students link clinical experiences with formal learning and knowledge of the particular patient's patterns of responses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations